Effectiveness of Nitrous Oxide in External Cephalic Version on Success Rate: A Randomized Controlled Trial. Issue 4 (December 2020) - Douchez, V.; Esbelin, J.; Misbert, E.; Arthuis, C.; Drouard, A.; Badon, V.; Fenet, O.; Thubert, T.; Winer, N.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:391–398) Successful external cephalic version (ECV) can reduce the likelihood of cesarean delivery and other adverse outcomes. Both the overall rate of ECV and the success rate may be increased by decreasing the pain involved in ECV. Regional anesthesia is effective in ECV but has some negative effects. Nitrous oxide is less invasive and is used during labor. This study aimed to assess the success rate of ECV with nitrous oxide mixed with oxygen (N2 O/O2 ).